2016
DOI: 10.1007/s11069-016-2224-1
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release inhibitor for preventing the spontaneous combustion of coal

Abstract: The existing coal self-heating inhibitors usually have the shortcomings of short effective time and low inhibition effect. This study proposed a kind of controlled-release inhibitor and analyzed their differences in inhibition effects compared with existing inhibitors on coal self-heating. The controlled-release inhibitor is made from the synthesis of halogen inhibitors, catechin, copolymer, solvent and surfactant. The controlled-release inhibitor will not break down quickly until coal temperature reaches a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…With the loss of water, their inhibition efficiency is greatly decreased (Li et al, 2012b). In maintaining the high efficiency of inhibiting spontaneous coal combustion, the application of temperature sensitive materials as coating to allow the release of inhibitors at a specific temperature was investigated (Cui et al, 2017;Li et al, 2016a;Ma et al, 2016Ma et al, , 2017Qi et al, 2016). However, they did not consider the effect of diffusion and action range of inhibitors, and it was found that the covered area of coal was extremely limited after solid or liquid inhibitors were released.…”
Section: Introductionmentioning
confidence: 99%
“…With the loss of water, their inhibition efficiency is greatly decreased (Li et al, 2012b). In maintaining the high efficiency of inhibiting spontaneous coal combustion, the application of temperature sensitive materials as coating to allow the release of inhibitors at a specific temperature was investigated (Cui et al, 2017;Li et al, 2016a;Ma et al, 2016Ma et al, , 2017Qi et al, 2016). However, they did not consider the effect of diffusion and action range of inhibitors, and it was found that the covered area of coal was extremely limited after solid or liquid inhibitors were released.…”
Section: Introductionmentioning
confidence: 99%
“…Dou et al studied a type of slow‐release controllable material for inhibiting spontaneous combustion of coal. In addition, Qi et al proposed that natural antioxidants, such as tea polyphenols, can also be used to inhibit coal oxidation. Xue and Hu believed that polymer hydrogels have broad application prospects in the field of fire prevention and fire extinguishing in coal mines.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [10] selected six different types of antioxidants (oxygen-scavenger ascorbic acid, butylated hydroxytoluene, triphenyl phosphite, 2,2,6,6-tetramethyl-1-piperidine-noxyl free radical [TEMPO], edetic acid, and phytic acid) as inhibitors for low-temperature oxidation experiments, and found that TEMPO had the greatest inhibition effect. Qi et al [11] proposed a kind of controlled-release inhibitor that is made from the synthesis of halogen inhibitors, catechin, copolymers, solvents, and surfactants. Tang [12] used phosphates and MgCl 2 as synergistic inhibitors for suppressing the self-ignition of coal.…”
Section: Introductionmentioning
confidence: 99%